2019
DOI: 10.1002/ece3.5238
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analyses identify hybridization‐mediated nuclear evolution in newly discovered fungal hybrids

Abstract: Hybridization may be a major driver in the evolution of plant pathogens. In a high elevation Alpine larch stand in Montana, a novel hybrid fungal pathogen of trees originating from the mating of Heterobasidion irregulare with H. occidentale has been recently discovered. In this study, sequence analyses of one mitochondrial and four nuclear loci from 11 Heterobasidion genotypes collected in the same Alpine larch stand indicated that hybridization has increased allelic diversity by generating novel polymorphisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…Hybridization is now widely recognized to be an important evolutionary process which might play a crucial role in speciation (Gross and Rieseberg 2005;Mallet 2007;Schumer et al 2014;Taylor and Larson 2019). Hybridization followed by reproductive isolation has been reported to contribute to rapid speciation of yeast (Leducq et al 2016) and the same has been supposed to occur in some filamentous fungi (Kohn 2005;Gladieux et al 2014;Sillo et al 2019). Du et al (2012) reported the 85.2% of the species in the Esculenta Clade (including almost 90% of the Chinese species lineages) diversified and went through rapid speciation in East Asia since the middle Miocene, which might have contributed to the potential hybridization and gene transfer events detected in the Esculenta Clade.…”
Section: Conflicts Between Non-reproductive Genes (F1 and Igs) And Thmentioning
confidence: 99%
“…Hybridization is now widely recognized to be an important evolutionary process which might play a crucial role in speciation (Gross and Rieseberg 2005;Mallet 2007;Schumer et al 2014;Taylor and Larson 2019). Hybridization followed by reproductive isolation has been reported to contribute to rapid speciation of yeast (Leducq et al 2016) and the same has been supposed to occur in some filamentous fungi (Kohn 2005;Gladieux et al 2014;Sillo et al 2019). Du et al (2012) reported the 85.2% of the species in the Esculenta Clade (including almost 90% of the Chinese species lineages) diversified and went through rapid speciation in East Asia since the middle Miocene, which might have contributed to the potential hybridization and gene transfer events detected in the Esculenta Clade.…”
Section: Conflicts Between Non-reproductive Genes (F1 and Igs) And Thmentioning
confidence: 99%
“…These results, and the weak cross‐reaction observed for H. occidentale DNA with the H. parviporum test, reflect the close phylogenetic relationship between these species that diverged quite recently (Chen et al , ). Future studies should therefore clarify the frequency of hybridization among Heterobasidion species and shed some light on their viability in natural populations, with the help of other nuclear markers, such as the ones used for recently described H. occidentale × H. irregulare hybrids (Sillo et al , ). However, the observation of double positive signals following the H. abietinum and H. parviporum real‐time PCR assays with some DNA from some of the H. parviporum pure cultures suggests caution, and it is recommended that all four species‐specific assays are run for the analysis of environmental samples.…”
Section: Discussionmentioning
confidence: 99%
“…However, their ecology and geographic distribution overlap to a large extent (Garbelotto & Gonthier, ) and they can co‐occur in the same stands (Gonthier et al , ; Sedlák & Tomšovský, ; Gonthier, ). In addition, several studies have shown incomplete species barriers between some species, with rare hybrids being found in forests (Garbelotto et al , ; Gonthier & Garbelotto, ; Sedlák & Tomšovský, ; Sillo et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Stukenbrock (2016) suggested that studies integrating genomic and experimental data are pivotal to understand the evolution of fungal hybrids in nature. Whereas fungal hybrid genotypes can be generated and studied in vitro (Olson and Stenlid 2001;Giordano et al 2018), hybrids resulting from natural selection are difficult to find in nature, given that only a few cases of ongoing hybridization are known (Garbelotto et al 1996;Gonthier and Garbelotto 2011;Hughes et al 2013;Pryszcz et al 2014;Menardo et al 2016;Sillo et al 2019).…”
Section: Introductionmentioning
confidence: 99%